Polyethylene blends
By preparing polyethylene blends with excellent characteristics, the benzene residue, poor mechanical properties and color problems in the recovery of polyethylene are solved, and high-quality polyethylene blends are achieved, suitable for bottle manufacturing and packaging, improving their medical care and application potential in the field of food packaging.
Patent Information
- Application Number
- CN202280037672.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-31
- Filing Date
- 2022-05-31
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-05-31
AI Technical Summary
The prior art has benzene residues, poor mechanical properties, color problems and insufficient uniformity in the recycling of polyethylene blends, resulting in limited application in medical packaging, food packaging and other fields, and the reuse of polyethylene after conventional consumption. Poor performance.
By preparing polyethylene blends with specific melt flow rate, density and chemical composition fractions, cross-fractionation chromatography and NMR measurement, the content and uniformity of the C2 fraction are improved and the aeration and washing process is reduced Inorganic residues and limonene content, control OCS gel counting and color, and enhance the mechanical and processing properties of the material.
Achieve high-quality polyethylene blends, which can directly replace the original polyethylene, have excellent mechanical properties, uniformity and color properties, and are suitable for bottle manufacturing and packaging, significantly improving its application in the fields of medical packaging and food packaging potential.
Smart Images

Figure BDA0004567988560000051 
Figure BDA0004567988560000061 
Figure BDA0004567988560000062
Abstract
Description
Technical Field
[0001] The present invention relates to polyethylene blends derived from recycled content. Background Art
[0002] Many attempts have been made to purify recycling streams from post-consumer waste. Among these measures, washing, screening, aeration, distillation, etc. can be mentioned. For example, WO2018046578 discloses a method for producing polyolefin recyclates from mixed color polyolefin waste including packaging waste, the method comprising washing the waste with water cooling, followed by washing with an alkaline medium at 60°C, followed by flake color sorting to receive color-classified (white, transparent, other colors) monopolyolefin-rich fractions. These fractions are then treated at 50 to 155°C. Welle, F. (2005). Develop, a food grade HDPE recycling process. The waste & Resources Action Programme, Oxon reports the recycling of milk bottles for the purpose of preparing food grade HDPE. US5767230A describes a method comprising contacting PCR polyolefin fragments containing volatile impurities with heated gas at a surface velocity sufficient to significantly reduce volatile impurities such as odor-active substances.
[0003] However, several problems remain: On the one hand, benzene is often found in post-consumer recyclates, the source of which remains suspicious, but is an obstacle to end uses in areas such as medical packaging, food packaging, etc. Residual amounts (i.e. trace amounts of benzene) constitute a particular problem because odor testing by sniffing experiments becomes impossible. Therefore, end uses with certain requirements for odor are prevented. On the second hand, the mechanical properties of conventional post-consumer polyethylene, such as notched impact performance of the Charpy (at 23°C and -20°C), ESCR, FNCT and drop test stability are quite poor, requiring expensive and unpopular improvement components. On the third hand, color is another legacy issue that has not yet been fully resolved. Many recycling applications require materials to be close to what is commonly called white or, alternatively, what is commonly called transparent. Another known problem is that post-consumer recyclates have moderate homogeneity, as reflected by excessively high OCS gel count levels.
[0004] Therefore, the problem of providing more valuable polyethylene blends remains. Summary of the invention
[0005] The present invention provides a polyethylene blend having
[0006] (i) a melt flow rate (ISO 1133, 5.0 kg; 190° C.) of 0.1 to 10 g / 10 min, preferably 0.5 to 5.0 g / 10 min, more preferably 0.7 to 4.0 g / 10 min, and most preferably 1.0 to 3.0 g / 10 min; and
[0007] (ii) 950 to 970 kg / m 3 density (ISO 1183); and
[0008] (iii) a C2 fraction of the d2-tetrachloroethylene soluble fraction as measured by NMR in an amount higher than 95.0 wt. %, preferably higher than 97.0 wt. %; and
[0009] (iv) a homopolymer fraction (HPF) content in the range of 80.0 to 91.0 wt % as determined by chemical composition analysis by cross fractionation chromatography (CFC); and
[0010] (v) a copolymer fraction (CPF) content in the range of 9.0 to 20.0 wt % as determined by chemical composition analysis cross fractionation chromatography (CFC); and
[0011] (vi) optionally, an iso-PP fraction (IPPF) content as determined by chemical composition analysis cross fractionation chromatography (CFC) in the range of 0 to 2.0 wt.%, preferably 0 to 0.5 wt.%, wherein the iso-PP fraction (IPPF) is defined as a polymer fraction eluted at a temperature of 104°C and above, wherein the homopolymer fraction (HPF), the copolymer fraction (CPF) and the iso-PP fraction (IPPF) add up to 100 wt.%; and
[0012] (vii) 0.01 to 2.00 wt. % inorganic residue (measured by TGA) relative to the total polyethylene blend; and
[0013] (viii) 500 to 5000 counts / m 2 The range of the OCS counting instrument is within 10m 2 OCS gel having a size of 100 to 299 microns measured on the film; wherein
[0014] (ix) The polyethylene blend has a CIELAB color space (L*a*b*) measured according to DIN EN ISO 11664-4:
[0015] - L* is from 75.0 to 86.0;
[0016] -a* is from -5.0 to 0.0;
[0017] -b* is from 5.0 to less than 25.0
[0018] or
[0019] (x) The polyethylene blend has a CIELAB color space (L*a*b*) measured according to DIN EN ISO 11664-4:
[0020] - L* is from greater than 86.0 to 97.0;
[0021] -a* is from -5.0 to 0.0;
[0022] -b* is from 0.0 to less than 5.0.
[0023] The invention also relates to a polyethylene blend in the form of particles. The invention further provides articles made from the polyethylene blend, in particular bottles, and the use of the polyethylene blend for packaging. In yet another aspect, the invention relates to a blend of the polyethylene blend with at least one virgin polyolefin and / or recycled polyolefin.
[0024] The term "polyethylene blend" is defined as the presence of at least two different polyethylenes, such as two high density polyethylenes of different densities. For example, bimodal polyethylene obtained from two reactors operating under different conditions constitutes a polyethylene blend, in this case an in situ blend of the two reactor products.
[0025] It goes without saying that the polyethylene blends obtained from consumer waste will include a variety of polyethylenes. In addition to this, contamination with other plastics can also be found, mainly polypropylene, polystyrene, polyamides, polyesters, wood, paper, limonene (also known as limonene), aldehydes, ketones, fatty acids, metals and / or long-term decomposition products of stabilizers. It goes without saying that such contaminants are undesirable.
[0026] It should be understood that the polyethylene blends of the present invention are not cookie cutter blends like some commercially available recyclates.The polyethylene blends according to the present invention should be compared to virgin blends.
[0027] The term "C2 fraction" refers to the quantitative 13 C{ 1 H} NMR spectroscopy measures the repeating -[C2H4]- units derived from ethylene, which are present in the linear backbone and short chain branches, where repeating means at least two units.
[0028] The C2 fraction can be calculated as
[0029] wt C2级分 =fC C2总 *100 / (fC C2总 +fCPP )
[0030] Among them, fC C2总 =(Iddg-ItwoB4)+(IstarB1*6)+(IstarB2*7)+(ItwoB4*9)+(IthreeB5*10)+((IstarB4plus-ItwoB4-IthreeB5)*7)+(I3s*3), and fC PP =Isαα*3.
[0031] Detailed information is given in the experimental section.
[0032] Since HDPE, LDPE or LLDPE, homopolymer and copolymer polyethylene are present in the recycled blend, analytical separation becomes a necessary condition for characterization. An appropriate method is the chemical composition analysis by cross-fractionation chromatography (CFC). This method has been described and successfully implemented by Polymer Char, Valencia Technology Par, Gustave Eiffel 8, Paterna E-46980 Valencia, Spain. The chemical composition analysis carried out by cross-fractionation chromatography (CFC) allows classification into homopolymer fraction (HPF) and copolymer fraction (CPF) and possible iso-PP fraction (IPPF). The homopolymer fraction (HPF) is a fraction that includes polyethylene similar to homopolymer-HDPE. The copolymer fraction (CPF) is a fraction similar to polyethylene HDPE copolymer, but it can also include fractions of LDPE and LLDPE, respectively. The iso-PP fraction (IPPF) includes isotactic polypropylene and is defined as the polymer fraction eluted at a temperature of 104°C and above. The homopolymer fraction (HPF), the copolymer fraction (CPF) and any iso-PP fraction (IPPF) add up to 100% by weight. It goes without saying that 100% by weight refers to the material which is soluble in a cross fractionation chromatography (CFC) experiment.
[0033] In addition to the chemical composition analysis by cross fractionation chromatography (CFC), the polyethylene blend according to the invention is characterized in that the amount of C2 fraction of the d2-tetrachloroethylene soluble fraction measured by NMR is higher than 95.0% by weight, preferably higher than 97.0% by weight. This percentage refers to the d2-tetrachloroethylene soluble part used for the NMR experiment. The term "C2 fraction" is equal to the polymer fraction obtainable from ethylene monomer units, i.e. not from propylene monomer units.
[0034] The upper limit of the "C2 fraction" is 100% by weight.
[0035] The present invention is based on the surprising finding that the polyethylene blends described herein allow for a direct replacement of virgin polyethylene.
[0036] The polyethylene blends according to the invention typically have a melt flow rate (ISO 1133, 5.0 kg; 190°C) of 0.1 to 10 g / 10 min. The melt flow rate may be affected by diversion of post-consumer plastic waste streams, for example, but not limited to: originating from extended producer responsibility systems, such as from the German DSD, or sorting municipal solid waste into a large number of pre-sorted fractions and recombining them in an appropriate manner. Typically, the MFR ranges from 0.5 to 5.0 g / 10 min, preferably from 0.7 to 4.0 g / 10 min, most preferably from 1.0 to 3.0 g / 10 min.
[0037] The amount of C2 fraction of the d2-tetrachloroethylene soluble fraction measured by NMR of the polyethylene blend according to the invention is higher than 95.0 wt.%, preferably higher than 97.0 wt.%, more preferably higher than 98.0 wt.%, most preferably higher than 99.0 wt.%.
[0038] Typically, the polyethylene blend according to the present invention is a recycled material.
[0039] Typically, recycling properties can be assessed by the presence of one or more of the following:
[0040] (1) an inorganic residue content exceeding 0.01 wt % (measured by TGA); and at the same time
[0041] Between 500 and 5000 counts / m 2 The range is 10 m by an OCS counting instrument (preferably OCS-FSA100, supplier OCSGmbH (Optical Control System)). 2 OCS gels with sizes ranging from 100 to 299 microns were measured on the film;
[0042] Alternatively or in combination
[0043] (2) 0.5 ppm or more of limonene as determined using solid phase microextraction (HS-SPME-GC-MS);
[0044] Alternatively or in combination
[0045] (3) Fatty acids consisting of acetic acid, butyric acid, valeric acid and caproic acid determined in a total amount of 10 ppm or more by using solid phase microextraction (HS-SPME-GC-MS).
[0046] It should be understood that options (2) and (3) are preferred. "Fatty acids consisting of the group consisting of acetic acid, butyric acid, valeric acid and caproic acid" means that the individual amounts of acetic acid, butyric acid, valeric acid and caproic acid (measured by HS-SPME-GC-MS in ppm) are added together.
[0047] The detection limit of limonene in solid phase microextraction (HS-SPME-GC-MS) was below 0.1 ppm, meaning that trace amounts of these substances could be easily determined for recovery properties.
[0048] It goes without saying that the amount of inorganic residues, gels, limonene and fatty acids should be as low as possible.
[0049] It is particularly preferred that limonene is present in an amount of 0.1 to 25 ppm, even more preferably 0.1 to 20 ppm, as determined by using solid phase microextraction (HS-SPME-GC-MS); and / or the total amount of fatty acids consisting of the group of acetic acid, butyric acid, valeric acid and caproic acid is present in a total amount of at least 10 to 500 ppm, more preferably 10 to 300 ppm, most preferably 10 to 180 ppm, as determined by using solid phase microextraction (HS-SPME-GC-MS).
[0050] With regard to color, two embodiments can be distinguished: an essentially colorless blend and an essentially white blend.
[0051] The first embodiment (substantially colorless) polyethylene blend has a CIELAB color space (L*a*b*) measured according to DIN EN ISO 11664-4:
[0052] - L* is from 75.0 to 86.0;
[0053] -a* is from -5.0 to 0.0;
[0054] - b* is from 5.0 to less than 25.0.
[0055] The second embodiment (substantially white) polyethylene blend has a CIELAB color space (L*a*b*) measured according to DIN EN ISO 11664-4:
[0056] - L* is from greater than 86.0 to 97.0;
[0057] -a* is from -5.0 to 0.0;
[0058] -b* is from 0.0 to less than 5.0.
[0059] The polyethylene blend according to the invention is preferably characterized by an odor value (VDA270-B3) of 2.5 or less, preferably 2.0 or less. It should be understood that many commercially available recycled grades that do not report an odor are in fact unacceptable in this respect, since the sniff test prescribed by VDA270 is prohibited due to the presence of problematic or toxic substances.
[0060] The polyethylene blends according to the present invention have the following OCS gel count properties (at 10 m 2 One or more of
[0061] a) Size 300 to 599 microns: 100 to 2500 counts / m 2 ;
[0062] b) Size 600 to 1000 microns: 5 to 200 counts / m 2 ;
[0063] c) Size over 1000 microns: 1 to 40 counts / m 2 .
[0064] OCS gel is expressed in counts per square meter, calculated as 10 m2 of the measured 2 Average value of the film.
[0065] In yet another aspect, the polyethylene blend according to the invention has a tensile modulus (ISO 527-2, at a crosshead speed of 1 mm / min; 23° C.) of at least 825 MPa, preferably at least 850 MPa, most preferably at least 910 MPa using an injection molded specimen as described in EN ISO 1873-2 (dog bone shape, 4 mm thickness). Typically the tensile modulus will not be higher than 1100 MPa.
[0066] It is also preferred that the polyethylene blend has no units derived from isotactic polypropylene when subjected to NMR analysis as described in the specification.
[0067] In yet another preferred aspect, the polyethylene blend according to the invention has a LAOS-NLF 1000% (190°C) of 2.1 to 2.9, preferably 2.2 to 2.7, and most preferably 2.3 to 2.6. LAOS-NLF 1000% is a rheological measure of the long chain branching content, defined as
[0068]
[0069] Among them, G1' is the first-order Fourier coefficient, and G3' is the third-order Fourier coefficient.
[0070] A rather moderate or low value of LAOS-NLF 1000% indicates a rather low, i.e. almost negligible amount of LDPE or LLDPE. LAOS-NLF furthermore indicates a non-linear polymer structure. In addition to sorting out LDPE and LLDPE, LAOS-NLF can also be influenced by blending various recycling streams (after the value has been determined) from different sources, e.g. from different states.
[0071] The polyethylene blend according to the present invention preferably has a shear thinning factor (STF) higher than 46.0, more preferably from 48.0 to 60.0.
[0072]
[0073] The shear thinning factor (STF) indicates the processability of polyethylene. The shear thinning factor (STF) can also be influenced by mixing the predetermined flows.
[0074] On the other hand, the polyethylene blend according to the present invention preferably has a polydispersity index (PI) higher than 2.0, more preferably from 2.1 to 2.7.
[0075]
[0076] Wherein Gc is the crossover modulus, which is the value of the shear storage modulus G' when the shear storage modulus G' is equal to the shear loss modulus G". The polydispersity index (PI) is a rheological measure of the width of the molecular weight distribution. From the viewpoint of processability, especially molding performance, higher values such as 2.0 or more, or in the range of 2.1 to 2.7 are preferred.
[0077] The polyethylene blend according to the present invention is preferably in the form of granules. Granulation helps to reduce the amount of volatile matter and helps homogenization.
[0078] The Charpy notched impact strength of the polyethylene blend according to the present invention is preferably higher than 35.0 kJ / m at 23°C. 2 , more preferably above 45 kJ / m at 23°C 2 At -20°C, the Charpy notched impact strength of the polyethylene blend according to the present invention is preferably higher than 18.0 kJ / m at 23°C. 2 , more preferably higher than 22 kJ / m 2 .
[0079] The yield tensile stress is preferably higher than 25.0 MPa.
[0080] On the other hand, the present invention relates to an article made of the polyethylene blend described herein. Preferably, the polyethylene blend according to the present invention accounts for at least 95% by weight of the reactants used to make the article. The article is preferably a bottle. In a preferred aspect, the polyethylene blend according to the present invention accounts for 95% to 98% by weight of the reactants used to make the article. Preferably, the article is made only of the polyethylene blend according to the present invention and an additive. In this embodiment, the additive is preferably selected from the group consisting of a UV stabilizer, an antioxidant and / or an acid scavenger.
[0081] In yet another aspect, the invention relates to a blend comprising the polyethylene blend described herein and at least one virgin and / or recycled polyolefin.For example, virgin polyethylene homopolymers may be blended.
[0082] The present invention also relates to the polyethylene blends described herein for use in packaging. DETAILED DESCRIPTION
[0083] The method for providing the polyethylene blend according to the present invention is quite demanding. The method comprises the following steps:
[0084] a) providing post-consumer plastic waste preferably from a separate waste collection containing polyethylene or municipal solid waste;
[0085] b) Sorting out items made of polystyrene, polyamide, polypropylene, metal, paper and wood, thus providing post-consumer plastic materials;
[0086] c) sorting out colored items, thereby providing a post-consumer plastic material mainly comprising white bottles, white yogurt cups, white jars, colorless panels, colorless component parts, etc., and steps b) and c) can be combined or performed separately;
[0087] d) optionally sorting out foreign matter by manual inspection;
[0088] e) receiving therefrom two streams of polyethylene material, a first stream being substantially transparent and a second stream being substantially white;
[0089] f) grinding the two streams separately, washing in aqueous solutions with various detergents and subsequently drying, windsifting and screening to produce two pretreated streams;
[0090] g) subjecting the two pretreated streams (together; separately) to further sorting to eliminate non-polyolefin and color fractions;
[0091] h) extruding into granules;
[0092] i) optionally performing aeration, preferably by preheating the post-consumer plastic material to a temperature in the range of 100 to 130°C using an air stream having a temperature of at least 100°C for at least 7 hours or preferably at least 20 hours at this temperature.
[0093] Aeration is usually required but can be skipped in specific circumstances.
[0094] Odor control and assessment can be achieved by a variety of methods. Demets, Ruben, et al. "Development and application of an analytical method to quantify odour removal in plastic waste recycling processes." Resources, Conservation and Recycling 161 (2020): 104907 also provides an overview, which is incorporated herein by reference.
[0095] The present invention relates to
[0096] The polyethylene blend as described herein can be obtained by the following steps:
[0097] a) providing post-consumer plastic waste preferably from a separate waste collection containing polyethylene or municipal solid waste;
[0098] b) Sorting out items made of polystyrene, polyamide, polypropylene, metal, paper and wood, thus providing post-consumer plastic materials;
[0099] c) sorting out the colored articles, thereby providing a first intermediate stream of substantially colorless products and a second intermediate stream of substantially white products;
[0100] d) optionally sorting out foreign matter by manual inspection;
[0101] e) receiving therefrom two streams of polyethylene material, a first stream being substantially transparent and a second stream being substantially white;
[0102] f) grinding the two streams separately, washing in aqueous solutions with various detergents and subsequently drying, air screening and screening to produce two pretreated streams;
[0103] g) further sorting the two pre-treated streams to eliminate non-polyolefin and colored fractions respectively;
[0104] h) extruding into granules;
[0105] i) optionally aerating at a temperature in the range of 100 to 130°C.
[0106] If necessary, inorganic residues can be reduced by solution technology. OCS gel count parameters can be controlled to avoid contaminants, such as pigments from colored materials, etc. Preferably, manual sorting is assisted by NIR spectroscopy, which is easily available in the form of small portable equipment. This allows the polypropylene content to be suppressed to a minimum. The density can be affected by reducing the amount of relatively flexible polyethylene products. The relative amount of homopolymer fraction (HPF) and copolymer fraction (CPF) can be controlled by wind shifting (the machine is also called an airflow sorter): using an airflow, the material is separated into various streams according to the size, shape and especially weight of the particles. For example, polyethylene film (i.e. LLDPE / LDPE with a relatively high copolymer fraction (CPF)) can be eliminated. CIELAB is controlled by combining color sorting with the elimination of non-polyethylene polymer impurities.
[0107] experiment
[0108] The following examples are included to demonstrate certain aspects and embodiments of the present invention as described in the claims. However, it should be understood by those skilled in the art that the following description is exemplary only and should not be viewed in any way as limiting the present invention.
[0109] Test Method
[0110] a) MFR
[0111] The melt flow rate is measured at 190° C. with a load of 5.00 kg (MFR5). The melt flow rate is the amount of polymer in grams which a test apparatus conforming to ISO 1133 standard extrude in 10 minutes at a temperature of 190° C. and a load of 5.00 kg.
[0112] b) Density
[0113] According to ISO 1183-1.
[0114] c) C2 fraction measured by NMR spectroscopy and general microstructure including "continuous C3" as well as short chain branches
[0115] Use for 1 H and 13 Quantitative measurements were recorded in solution on a Bruker AVNEO 400 MHz NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatic devices and the temperature was 125 °C. 13All spectra were recorded with a 10 mm extended temperature probe optimized for C. About 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) along with about 3 mg of BHT (2,6-di-tert-butyl-4-methylphenol, CAS 128-37-0) and chromium-(III) acetylacetonate (Cr(acac)3) to give a 60 mM solution of the relaxation agent in the solvent {singh09}. To ensure the homogeneity of the solution, the NMR tube was further heated in a rotary oven for at least 1 hour after the initial sample preparation in the heating block. After insertion into the magnet, the tube was rotated at 10 Hz. Standard single pulse excitation without NOE was employed, using an optimized tip angle, a recycle delay of 1 s and a two-stage WALTZ16 decoupling scheme {zhou07, busico07}. A total of 6144 (6k) transient signals were collected for each spectrum.
[0116] A proprietary computer program was used to quantify 13 C{ 1 H} NMR spectra were processed, integrated and relevant quantitative properties were determined from the integrals. All chemical shifts were indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. Characteristic signals corresponding to polyethylene and polypropylene with different short chain branches (B1, B2, B4, B5, B6plus) were observed {randall89, brandolini00}.
[0117] Observed and comprise isolated B1 branch (starBI 33.3ppm), isolated B2 branch (starB2 39.8ppm), isolated B4 branch (twoB4 23.4ppm), isolated B5 branch (threeB5 32.8ppm), all branch (starB4plus 38.3ppm) longer than 4 carbons and the characteristic signal corresponding to the presence of the polyethylene of the third carbon (3s 32.2ppm) of the saturated aliphatic chain end. If one or another structural element is not observable, it is excluded from the equation. The intensity of the combined ethylene main chain second methyl carbon (ddg) comprising polyethylene main chain carbon (dd 30.0ppm), γ-carbon (g 29.6ppm), 4s and threeB4 carbon (compensated later) is between 30.9ppm and 29.3ppm, excluding Tββ from polypropylene. Use all mentioned signals to quantify the amount of C2 related carbon according to the following equation:
[0118] f C2总=(Iddg-ItwoB4)+(IstarB1*6)+(IstarB2*7)+(ItwoB4*9)+(IthreeB5*10)+((IstarB4plus-ItwoB4-IthreeB5)*7)+(I3s*3)
[0119] While characteristic signals corresponding to the presence of polypropylene (PP, continuous C3) were observed at 46.7 ppm, 29.0 ppm, and 22.0 ppm, the amount of PP-related carbon was quantified using the integration of Sαα at 46.6 ppm:
[0120] f PP =Isαα*3
[0121] The weight percentages of C2 fraction and polypropylene can be quantified according to the following equations:
[0122] wt C2级分 =fC C2总 *100 / (fC C2总 +fC PP )
[0123] wt PP =fC PP *100 / (fC C2总 +fC PP )
[0124] Characteristic signals corresponding to various short chain branches were observed, and their weight percentages were quantified. Since the relevant branches should be α-olefins, the weight fraction of each branch was first quantified:
[0125] fwtC2=fC C2总 -(IstarB1*3)-(IstarB2*4)-(ItwoB4*6)-(IthreeB5*7)
[0126] fwtC3(isolated C3)=IstarB1*3
[0127] fwtC4=IstarB2*4
[0128] fwtC6=ItwoB4*6
[0129] fwtC7=IthreeB5*7
[0130] Normalization of all weight fractions yields the amount of weight percentage of all relevant branches:
[0131] f and 重量%总 =fwtC2+fwtC3+fwtC4+fwtC6+fwtC7+fC PP
[0132] wtC2total=fwtC2*100 / ftotal 重量%总
[0133] wtC3total=fwtC3*100 / ftotal 重量%总
[0134] wtC4total=fwtC4*100 / ftotal 重量%总
[0135] wtC6total = fwtC6*100 / ftotal 重量%总
[0136] wtC7total=fwtC7*100 / f 重量%总
[0137] zhou07
[0138] Zhou,Z.,Kuemmerle,R.,Qiu,X.,Redwine,D.,Cong,R.,Taha,A.,Baugh,D.Winniford,B.,J.Mag.Reson.187(2007)225
[0139] busico07
[0140] Busico,V.,Carbonniere,P.,Cipullo,R.,Pellecchia,R.,Severn,J.,Talarico,G.,Macromol.Rapid Commun.2007,28,1128
[0141] singh09
[0142] Singh,G.,Kothari,A.,Gupta,V.,Polymer Testing 28 5(2009),475
[0143] randall89
[0144] J. Randall, Macromol. Sci., Rev. Macromol. Chem. Phys. 1989, C29, 201.
[0145] brandolini00
[0146] AJ Brandolini, DDHills, NMR Spectra of Polymers and PolymerAdditives, Marcel Dekker Inc., 2000
[0147] d) Polymer composition analysis by CFC - determination of homopolymer fraction (HPF), copolymer fraction (CPF) and iso-PP fraction (IPPF)
[0148] The chemical composition distribution at a specific elution temperature (polymer crystallinity in solution) and the determination of the molecular weight distribution and the corresponding molecular weight averages (Mn, Mw and Mv) were determined by fully automated cross-fractionation chromatography (CFC) as described by Ortin A., Monrabal B., Sancho-Tello J., Macromol. Symp., 2007, 257, 13-28.
[0149] Cross-fractionation chromatography (TREF xSEC) was performed using a CFC instrument (PolymerChar, Valencia, Spain). The concentration was monitored using a quad band IR5 infrared detector (PolymerChar, Valencia, Spain). The polymer was dissolved at a concentration of approximately 0.4 mg / ml at 160°C for 180 minutes.
[0150] To avoid injection of possible gels and polymers that are not soluble in TCB at 160°C, such as PET and PA, the weighed samples were loaded into a stainless steel mesh of MW 0.077 / D 0.05 mm.
[0151] After the sample was completely dissolved, a 0.5 ml aliquot was loaded into the TREF column and stabilized at 110° C. for 60 minutes. The polymer was crystallized and precipitated to a temperature of 60° C. by applying a constant cooling rate of 0.07° C. / min. The discontinuous elution process was performed using the following temperature steps: (60, 65, 69, 73, 76, 79, 80, 82, 85, 87, 89, 90, 91, 92, 93, 94, 95, 95, 96, 97, 98, 99, 100, 102, 104, 107, 120, 130).
[0152] In the second dimension, GPC analysis, 3 PL Olexis columns and 1x Olexis guard columns from Agilent (Church Stretton, UK) were used as stationary phase. As eluent, 1,2,4-trichlorobenzene (TCB, stabilized with 250 mg / L of 2,6-di-tert-butyl-4-methylphenol) was applied at a constant flow rate of 1 mL / min at 150 °C. The column set was calibrated using universal calibration (according to ISO16014-2:2003) using at least 15 narrow MWD polystyrene (PS) standards in the range of 0.5 kg / mol to 11500 kg / mol. Subsequently, the PS molecular weight was converted to PE molecular weight equivalent using Mark Houwink constants.
[0153] K PS =19x 10 -3 mL / g, α PS =0.655
[0154] K PE =39x 10 -3 mL / g, α PP =0.725
[0155] A third order polynomial fit was used to fit the calibration data. Data processing was performed using the software provided by PolymerChar with the CFC instrument.
[0156] The homopolymer fraction (HPF) and the copolymer fraction (CPF) as well as the iso-PP fraction (IPPF) were calculated.
[0157] The homopolymer fraction (HPF), copolymer fraction (CPF) and iso-PP fraction (IPPF) are defined as follows:
[0158] 100% = CPF + HPF + IPPF
[0159] The IPPF fraction is defined as the polymer fraction eluted at 104°C and above.
[0160] Since the TREF curve has a slight dependence on the low MW portion, the molecular weight limit of the low MW limit is related to the elution temperature (T el ). The lower MW limit is determined using the following formula:
[0161] Low MW limit (for HPF fraction) = 0.0125*T el +2.875
[0162] Taking this into account, the HPF fraction was calculated using the following method.
[0163]
[0164] Among them, H ij is the corresponding elution temperature (T el )i and 2D differential distribution at logM value j.
[0165] e) Inorganic residues
[0166] The inorganic residues were determined by TGA according to DIN ISO 11358-1:2014 using a TGA Discovery TGA5500. Approximately 10 to 30 mg of material were placed in a platinum pan. The sample was heated under nitrogen at a heating rate of 20°C / min. The ash content was evaluated in wt% at 850°C.
[0167] f) OCS gel
[0168] Cast film samples with a thickness of about 70 μm were extruded and inspected using a CCD (charge coupled device) camera, image processor and evaluation software (instrument: OCS-FSA100, supplier OCS GmbH (Optical Control Systems)). Film defects were measured and classified according to their circle diameter. Analysis of 10 m 2 of film and calculated the value per square meter as an average.
[0169] Cast film preparation, extrusion parameters:
[0170] 1. Output 25±4g / min
[0171] 2. Extruder temperature curve: 200-210-210-200 (melt temperature 224°C)
[0172] 3. Film thickness is about 70μm
[0173] 4. Cooling roller temperature 80℃
[0174] 5. Air knife 6400NI / h (volume)
[0175] Extruder technical data:
[0176] 1. Screw type: 3-zone, nitrification
[0177] 2. Screw diameter: 25mm
[0178] 3. Screw length: 25D
[0179] 4. Feeding area: 10D
[0180] 5. Compression area: 4D + output area 11D
[0181] 6. Die head 150mm
[0182] Defects by size (μm) / m2 To classify:
[0183] 100-299μm
[0184] 300-599μm
[0185] 600-999μm
[0186] 1000μm and higher
[0187] g) CIELAB color space (L*a*b*)
[0188] In the CIE L*a*b* uniform color space measured according to DIN EN ISO 11664-4, the color coordinates are: L* — lightness coordinate; a* — red / green coordinate, where +a* represents red and -a* represents green; b* — yellow / blue coordinate, where +b* represents yellow and -b* represents blue. The L*, a* and b* coordinate axes define the three-dimensional CIE color space. Standard Konica / Minolta colorimeter CM-3700A.
[0189] h) Evaluation of recycling properties
[0190] ha) Limonene content
[0191] Limonene quantification can be performed using solid phase microextraction (HS-SPME-GC-MS) by standard addition.
[0192] 50 mg of ground sample was weighed in a 20 mL headspace vial and the vial was sealed with a silicone / PTFE lined magnetic cap after adding different concentrations of limonene and a glass coated magnetic stir bar. Diluted limonene standards of known concentrations were added to the samples using a microcapillary (10 pL). 0, 2, 20 and 100 ng were added corresponding to 0 mg / kg, 0.1 mg / kg, 1 mg / kg and 5 mg / kg limonene, in addition standard amounts of 6.6 mg / kg, 11 mg / kg and 16.5 mg / kg limonene were used in conjunction with some of the samples tested in this application. Quantification was performed using ion-93 acquired in SIM mode. Volatile components were enriched by headspace solid phase microextraction using a 2 cm stable curved 50 / 30 pm DVB / Carboxen / PDMS fiber at 60 °C for 20 min. Desorption was performed directly in the heated injection port of the GCMS system at 270 °C.
[0193] GCMS parameters:
[0194] Column: 30m HP 5MS 0.25*0.25
[0195] Injector: Splitless, with 0.75 mm SPME liner, 270 °C
[0196] Temperature program: -10℃(1min)
[0197] Carrier gas: Helium 5.0, 31cm / s linear velocity, constant flow
[0198] MS: Single quadrupole, direct interface, interface temperature 280°C
[0199] Acquisition: SIM scan mode
[0200] Scan parameters: 20 to 300amu
[0201] SIM parameters: m / Z 93, 100 ms dwell time
[0202] HB fatty acid detection
[0203] Fatty acid quantification was performed using headspace solid phase microextraction (HS-SPME-GC-MS) by standard addition.
[0204] 50 mg of ground sample was weighed in a 20 mL headspace vial and sealed with a silicone / PTFE lined magnetic cap after adding different concentrations of limonene and a glass coated magnetic stir bar. A known concentration of a diluted free fatty acid mixture (acetic, propionic, butyric, valeric and hexanoic acids, optional octanoic acid) standard was added to the sample at three different levels using a 10 μL microcapillary. The addition of 0, 50, 100 and 500 ng was equivalent to 0 mg / kg, 1 mg / kg, 2 mg / kg and 10 mg / kg of each individual acid. All acids except propionic acid (here ion 74 was used) were quantified using ion 60 collected in SIM mode.
[0205] GCMS parameters:
[0206] Column: 20m ZB Wax plus 0.25*0.25
[0207] Injector: Split 5:1, glass lined with split liner, 250°C
[0208] Temperature program: 40℃(1min)@6℃ / min to 120℃, @15℃ to 245℃(5min)
[0209] Carrier gas: Helium 5.0, 40 cm / s linear velocity, constant flow
[0210] MS: Single quadrupole, direct interface, interface temperature 220°C
[0211] Acquisition: SIM scan mode
[0212] Scan parameters: 46 to 250 amu 6.6 scans / second
[0213] SIM parameters: m / z 60, 74, 6.6 scans / sec
[0214] hc) Metal
[0215] Determined by x-ray fluorescence (XRF).
[0216] hd) Benzene content
[0217] The results were determined by HS GC-MS at 80°C / 2h, as described below:
[0218] Static Headspace Analysis
[0219] The parameters of the applied static headspace gas chromatography mass spectrometry (HS / GC / MS) method are described here.
[0220] Weigh 4.000 ± 0.100 g of sample in a 20 ml HS vial and seal tightly with a PTFE cap.
[0221] The mass spectrometer was operated in scan mode and a total ion chromatogram (TIC) was recorded for each analysis. Further details on applicable method parameters and data evaluation are given below:
[0222] -HS parameters (Agilent G1888 headspace sampler)
[0223] Bottle balancing time: 120min
[0224] Oven temperature: 80℃
[0225] Circuit temperature: 205℃
[0226] Transfer line temperature: 210°C
[0227] Low vibration
[0228] -GC parameters (Agilent 7890AGC system)
[0229] Column: ZB-WAX 7HG-G007-22 (30m×250μm×1μm)
[0230] Carrier gas: Helium 5.0
[0231] Flow rate: 2ml / min
[0232] Split ratio: 5:1
[0233] GC oven program: 35°C, last 0.1 min
[0234] 10℃ / min up to 250℃
[0235] 250℃, 1min
[0236] -MS parameters (Agilent 5975C inert XL MSD)
[0237] Acquisition Mode: Scan
[0238] Scan parameters:
[0239] Low Quality: 20
[0240] High quality: 200
[0241] Threshold: 10
[0242] - Software / Data Evaluation
[0243] MSD ChemStation E.02.02.1431
[0244] MassHunter GC / MS Acquisition B.07.05.2479
[0245] AMDIS GC / MS Analysis Version 2.71
[0246] NIST Mass Spectral Library Version 2.0g
[0247] -AMDIS deconvolution parameters
[0248] Minimum matching factor: 80
[0249] Threshold: Low
[0250] Scan direction: from high to low
[0251] Data file format: Agilent files
[0252] Instrument Type: Quadrupole
[0253] Component width: 20
[0254] Adjacent peak subtraction: two
[0255] Resolution: High
[0256] Sensitivity: Very high
[0257] Shape requirements: Medium
[0258] Solvent tailing: 44m / z
[0259] Column bleed: 207m / z
[0260] Minimum model peak: 2
[0261] Minimum S / N: 10
[0262] Lowest specific peak: 0.5
[0263] Data evaluation
[0264] The TIC data was further deconvoluted using the AMDIS software (see the above parameters) and compared with a custom target library based on a mass spectrometry library (NIST). The custom target library includes the corresponding mass spectra of the selected substances (e.g., benzene). A substance is only accepted as "preliminarily identified" if the identified peak shows a minimum match factor of 80 and is confirmed by an experienced mass spectrometrist.
[0265] In this study, the expression "below the detection limit (<LOD)" refers to the case where the match factor is below 80 (AMDIS) or the peak itself cannot even be identified. The results only relate to the measured samples, the measurement time, and the applied parameters.
[0266] i) Odor VDA270-B3
[0267] VDA 270 is used to determine the odor characteristics of motor vehicle trim materials. The odor is determined according to VDA 270 (2018) variant B3. After lifting the lid of the can as little as possible, each assessor evaluates the odor of the corresponding sample according to the VDA 270 scale. The six-level scale consists of the following grades: Grade 1: Not perceptible, Grade 2: Perceptible, not disturbing, Grade 3: Clearly perceptible, but not disturbing, Grade 4: Disturbing, Grade 5: Strongly disturbing, Grade 6: Unacceptable. The assessors remain calm during the evaluation and are not allowed to discuss the individual results with each other during the test so as not to be biased. They are also not allowed to adjust their evaluations after testing another sample. For statistical reasons (and accepted by VDA 270), the assessors are forced to use the entire step in their evaluations. Therefore, the odor grade is based on the average of all individual evaluations and is rounded to an integer.
[0268] j) Tensile modulus and elongation at break
[0269] Using the injection-molded specimens (dog-bone shape, 4 mm thickness) described in EN ISO 17855-2, the measurement was carried out according to ISO 527-2 (crosshead speed = 1 mm / min; at 23 °C, test speed 50 mm / min). The measurement was carried out after the specimens had been conditioned for 96 h.
[0270] k) Impact strength
[0271] Determined as Charpy notched impact strength (1 eA) according to ISO 179-1 eA at +23°C and -20°C on 80 x 10 x 4 mm injection moulded specimens prepared according to EN ISO 1873-2 (non-instrumented).
[0272] l) Rheological parameters
[0273] Dynamic shear measurement
[0274] The characterization of the polymer melts by dynamic shear measurements complies with ISO standards 6721-1 and 6721-10. The measurements are carried out on an Anton Paar MCR501 stress-controlled rotational rheometer equipped with a 25 mm parallel plate geometry. The measurements are carried out on compression molded plates, using a nitrogen atmosphere and setting the strain in the linear viscoelastic range. The oscillatory shear tests are completed at 190°C with frequencies between 0.01 and 600 rad / s and a gap of 1.3 mm.
[0275] In a dynamic shear experiment, the probe is uniformly deformed under a sinusoidally varying shear strain or shear stress (strain and stress controlled modes, respectively). In a controlled strain experiment, the probe is subjected to a sinusoidal strain, which can be expressed by
[0276] γ(t)=γ0 sin(ωt) (1)
[0277] If the applied strain is within the linear viscoelastic range, the resulting sinusoidal stress response can be given by
[0278] σ(t)=σ0 sin(ωt+δ) (2)
[0279] in
[0280] σ0 and γ0 are stress and strain amplitudes, respectively
[0281] ω is the frequency and δ is the angle.
[0282] t is the time
[0283] Dynamic test results are usually expressed by several different rheological functions, namely, shear storage modulus G', shear loss modulus G", complex shear modulus G*, complex shear viscosity η*, dynamic shear viscosity η', heterogeneous component of complex shear viscosity η" and loss tangent tanδ, which can be expressed by the following formula:
[0284]
[0285]
[0286] G *=G′+ iG″ [Pa] (5)
[0287] η * =η′-iη″ [Pa.s] (6)
[0288]
[0289]
[0290] ETA (x kPa) is determined according to Equation 9.
[0291] For (G * =x kPa), ETA (x kPa) = Eta * [Pa.s](9)
[0292] For example, ETA(2.7 kPa) is defined by the complex viscosity value determined for a complex modulus value equal to 2.7 kPa.
[0293] Eta (x rad / s) is determined according to Equation 10.
[0294] For (ω = x rad / s), ETA (x rad / s) = Eta * [Pa.s](10)
[0295] For example, ETA(300 rad / s) is defined by the complex viscosity value determined at a frequency sweep of 300 rad / s.
[0296] Shear Thinning Factor (STF) and Polydispersity Index (PI)
[0297] The shear thinning factor (STF) is defined as
[0298]
[0299] The polydispersity index (PI) is defined as
[0300]
[0301] Where Gc is the crossover modulus, which can be described as the value of the shear storage modulus G' when the shear storage modulus G' is equal to the shear loss modulus G".
[0302] These values were determined by a single-point interpolation procedure, as defined in the Rheoplus software. In cases where a given G* value was not reached experimentally, it was determined by extrapolation using the same procedure as before. In both cases (interpolation or extrapolation), the Rheoplus options "-Interpolate y values to x values from parameters" and "Logarithmic interpolation type" were applied.
[0303] References:
[0304] [1]Rheological characterization of polyethylene fractions” Heino, EL, Lehtinen, A., Tanner J., J.,Neste Oy,Porvoo,Finland,Theor.Appl.Rheol.,Proc.Int.Congr.Rheol,11th(1992),1,360-362
[0305] [2]The influence of molecular structure on some rheologicalproperties of polyethylene", Heino, EL, Borealis Polymers Oy, Porvoo, Finland, Annual Transactions of the Nordic Rheology Society, 1995.).
[0306] [3]Definition of terms relating to the non-ultimate mechanicalproperties of polymers,Pure&Appl.Chem.,Vol.70,No.3,pp.701-754,1998.
[0307] Large Amplitude Oscillatory Shear (LAOS)
[0308] The nonlinear viscoelastic behavior under shear flow has been investigated using large amplitude oscillatory shear. The method requires the application of a sinusoidal strain amplitude γ0 for a given time t at a given angular frequency ω. If the applied sinusoidal strain is high enough, a nonlinear response will result. In this case, the stress σ is a function of the applied strain amplitude, time, and angular frequency. Under these conditions, the nonlinear stress response is still a periodic function; however, it can no longer be represented by a single harmonic sinusoid. The stress resulting from the nonlinear viscoelastic response [0-0] can be represented by a Fourier series, which includes higher harmonic contributions:
[0309] σ(t,ω,γ0)=γ0.∑ n [G′ n (ω,γ0).sin(nωt)+G″ n (ω,γ0).cos(nωt)] (1)
[0310] Where, σ-stress response
[0311] t-time
[0312] ω-Frequency
[0313] γ0-strain amplitude
[0314] n - number of harmonics
[0315] G' n -nth order elastic Fourier coefficient
[0316] G” n -nth order viscosity Fourier coefficient
[0317] Large amplitude oscillatory shear (LAOS) was applied to analyze the nonlinear viscoelastic response. Time sweep measurements were performed on an RPA 2000 rheometer from Alpha Technologies connected to a standard double cone die. During the measurements, the test chamber was sealed and a pressure of approximately 6 MPa was applied. LAOS tests were completed at an applied temperature of 190°C, an angular frequency of 0.628 rad / s and a strain of 1000%. To ensure that steady-state conditions were achieved, the nonlinear response was determined only after at least 20 cycles were completed for each measurement. The large amplitude oscillatory shear nonlinear factor (LAOS_NLF) is defined as:
[0318]
[0319] Among them, G1'-first-order Fourier coefficient, G3'-third-order Fourier coefficient
[0320] [1]JMDealy, KFWissbrun, Melt Rheology and Its Role in PlasticsProcessing: Theory and Applications; edited by Van Nostrand Reinhold, New York (1990)
[0321] [2]S.Filipe,Non-Linear Rheology of Polymer Melts,AIP ConferenceProceedings 1152,pp.168-174(2009)
[0322] [3]M.Wilhelm,Macromol.Mat.Eng.287,83-105(2002)
[0323] [4]S.Filipe,K.Hofstadler,K.Klimke,ATTran,Non-Linear RheologicalParameters for Characterization of Molecular Structural Properties inPolyolefins,Proceedings of Annual European Rheology Conference,135(2010)
[0324] [5]S.Filipe,K.Klimke,ATTran,J.Reussner,Proceedings of Novel Non-Linear Rheological Parameters for Molecular Structural Characterization ofPolyolefins,Novel Trends in Rheology IV,Zlin,Check Republik(2011)
[0325] [6] K.Klimke, S.Filipe, ATTran, Non-linear rheological parameters for characterization of molecular structural properties in polyolefins, Proceedings of European Polymer Conference, Granada, Spain (2011)
[0326] Bottle production:
[0327] A 1 L bottle with an outer diameter of 90 mm, a wall thickness of 0.6 mm, an overall height of 204 mm and a cylindrical hood height of 185 mm was produced by extrusion blow molding on a B&W machine with a single screw extruder using a melt temperature of 190°C and a mold temperature of 15°C.
[0328] Bottle drop test (progressive):
[0329] In the progressive drop test, each bottle defined above is dropped several times in succession from increasing heights. For each bottle, the test is stopped when breakage occurs.
[0330] Drop tests were performed on 1 L bottles extrusion blow moulded as described previously. The bottles were filled to the shoulder with water.
[0331] At least 12 bottles are required for each test series. 4 bottles are dropped simultaneously from a starting height selected according to the following table, where the expected breakage drop height has been determined in a preliminary test or selected empirically:
[0332] Expected rupture drop height (m) 0.3-1-0 1.0-2.5 2.5-5.0 Initial drop height (m) 0.2 0.5 2.0
[0333] Those bottles that break are discarded and the test is continued with the remaining bottles at a higher height. The size of the step size of the height increase depends on the starting height. When the starting height is below 0.5m, the step size is 0.1m, while when the starting height is equal to or above 0.5m, the step size is 0.25m. The break drop height of each bottle is recorded and the average break drop height is calculated from the individual values according to the following formula:
[0334] h p =∑(h i ) / n g
[0335] Among them, h p = Average rupture drop height
[0336] h i = Each rupture drop height
[0337] n g = Total number of dropped containers
[0338] Example
[0339] Several post-consumer plastic waste HDPE streams from a separate plastic waste collection (a municipal facility site providing specific HDPE collection) were roughly sorted according to polymer properties and color. Impurities were further separated by manual inspection. The two streams of the colorless part (→IE1) and the white part (→IE2) thus received were (respectively) ground, washed in an aqueous solution with various detergents, and then dried and screened to produce a pretreated stream. The pretreated stream was further sorted to reduce the colored part and non-polyolefins. After extrusion into particles, the substrate particles were preheated to at least 100°C and the particles were aerated in air at 120°C for 22 hours. Essentially colorless Example IE1 and white Example IE2 were obtained. For comparison purposes, ordinary recyclate CE1 (Purpolen) and original bimodal polyethylene CE2 (an in-situ mixture of a low molecular weight homopolymer and a high molecular weight copolymer) were provided and tested. The results of the final material are shown in Table 1. The original bimodal polyethylene CE2 (an in-situ mixture of a low molecular weight homopolymer and a high molecular weight copolymer) used for comparative purposes was produced by polymerizing ethylene and a very small amount of 1-butene.
[0340] All examples were analyzed for polymer composition by CFC.
[0341] Table 1: Properties of the embodiments of the present invention and the comparative examples
[0342]
[0343]
[0344]
[0345] It can be seen that the performance of inventive examples IE1 and IE2 is almost as good as the virgin material. The inventive blends have significantly lower OCS gel counts compared to the standard recyclate blend.
[0346] The Charpy notched impact properties of the inventive examples IE1 and IE2 proved to be even better when compared to the original in-situ bimodal blend CE2. The yield tensile stress of IE1 and IE2 was at similar levels compared to CE2. IE1 and IE2 had excellent LAOS-NLF, shear thinning factor and polydispersity, indicating excellent processability.
[0347] IE1 and IE2 can be made into bottles, where these bottles have excellent qualities (uniformity of the wall, weld lines and outer surface smoothness). The processing properties of IE1 and IE2 even proved to be the best of all the evaluated materials. Bottles made of IE1 and IE2 even performed better than CE2 in the drop test.
[0348] In other words, for many applications, virgin bimodal polyethylene can be replaced in a 1:1 ratio, resulting in additional surprising advantages observed in terms of impact properties, processing properties and drop test stability of the bottles.
Claims
1. A polyethylene blend having (i) a melt flow rate measured under a load of 5.0 kg and 190° C. in accordance with ISO 1133 of 0.1 to 10 g / 10 min; and (ii) 950 to 970 kg / m 3 Density measured according to ISO 1183; and (iii) a C2 fraction of the d2-tetrachloroethylene soluble fraction measured by NMR in an amount greater than 95.0% by weight; and (iv) a homopolymer fraction content in the range of 80.0 to 91.0 wt % as determined by chemical composition analysis by cross-fractionation chromatography; and (v) a copolymer fraction content in the range of 9.0 to 20.0 wt % as determined by chemical composition analysis by cross-fractionation chromatography; and (vii) 0.01 to 2.00 wt. % inorganic residue as measured by TGA relative to the total polyethylene blend; and (viii) 500 to 5000 counts / m 2 The range of the OCS counting instrument is within 10m 2 OCS gels measuring 100 to 299 microns in size on the film; and in (ix) The polyethylene blend has a CIELAB color space L*a*b* measured according to DIN EN ISO 11664-4: - L* is from 75.0 to 86.0; -a* is from -5.0 to 0.0; -b* is from 5.0 to less than 25.0 or (x) The polyethylene blend has a CIELAB color space L*a*b* measured according to DIN EN ISO 11664-4: - L* is from greater than 86.0 to 97.0; -a* is from -5.0 to 0.0; -b* is from 0.0 to less than 5.0, The polyethylene blend is a recycled material, which can be obtained by the following steps: a) Provide post-consumer plastic waste; b) Sorting out items made of polystyrene, polyamide, polypropylene, metal, paper and wood, thus providing post-consumer plastic materials; c) sorting out the colored articles, thereby providing a first intermediate stream of substantially colorless products and a second intermediate stream of substantially white products; e) receiving therefrom two streams of polyethylene material, a first stream being substantially transparent and a second stream being substantially white; f) grinding the two streams separately, washing in aqueous solutions with various detergents and subsequently drying and screening to produce two pretreated streams; g) further sorting the two pretreated streams to eliminate non-polyolefin and colored fractions respectively; h) extrusion into granules; and wherein the polydispersity index of the polyethylene blend is from 2.1 to 2.7, Where Gc is the crossover modulus, which is the value of the shear storage modulus G' when the shear storage modulus G' is equal to the shear loss modulus G".
2. The polyethylene blend according to claim 1, having (vi) an iso-PP fraction content determined according to chemical component analysis by cross-fractionation chromatography in the range of 0 to 2.0 wt%, wherein the iso-PP fraction is defined as a polymer fraction eluted at a temperature of 104° C. and above, wherein the homopolymer fraction, the copolymer fraction and the iso-PP fraction add up to 100 wt%.
3. The polyethylene blend according to claim 1, wherein two streams are separately ground, washed in aqueous solutions with various detergents and then dried and air-sieved to produce two pre-treated streams.
4. The polyethylene blend according to claim 1, comprising one or more of the following: a) limonene in an amount of 0.1 to 25 ppm as determined by using solid phase microextraction HS-SPME-GC-MS; and b) Fatty acids consisting of the group of acetic acid, butyric acid, valeric acid and caproic acid determined by using solid phase microextraction HS-SPME-GC-MS in a total amount of 10 to 500 ppm.
5. The polyethylene blend according to any one of claims 1 to 4, having an odor value VDA270-B3 of 2.5 or less.
6. The polyethylene blend according to any one of claims 1 to 4 has the following 2 One or more of the OCS gel counting properties measured on a film of a) OCS gel with a size of 300 to 599 microns: 100 to 2500 counts / m 2 ; b) OCS gels with a size of 600 to 1000 microns: 10 to 200 counts / m 2 ; c) OCS gels with a size greater than 1000 μm: 1 to 40 counts / m 2 ; All are counted by OCS instrument within 10m 2 The measurements were performed on thin films.
7. The polyethylene blend according to any one of claims 1 to 4 having a tensile modulus of at least 825 MPa measured according to ISO 527-2 at a crosshead speed of 1 mm / min and at 23°C using injection molded specimens of dog-bone shape described in EN ISO 1873-2 with a thickness of 4 mm.
8. The polyethylene blend according to any one of claims 1 to 4, having no units derived from isotactic polypropylene when analyzed by NMR.
9. The polyethylene blend according to any one of claims 1 to 4, wherein the large amplitude oscillatory shear-nonlinear factor measured at 190°C and 1000% strain is in the range of 2.1 to 2.9, in, G1' is the first order Fourier coefficient and G3' is the third order Fourier coefficient.
10. The polyethylene blend according to any one of claims 1 to 4, wherein the shear thinning factor is higher than 46.0, Where (ω=0.05rad / s) Eta * Defined by the complex viscosity value determined under a frequency sweep of 0.05 rad / s, and Eta at (ω = 300 rad / s) * Defined by the complex viscosity value determined at a frequency sweep of 300 rad / s.
11. The polyethylene blend according to any one of claims 1 to 4, which can be obtained by the following steps: a) providing post-consumer plastic waste of high purity polyethylene from separate waste collection or municipal solid waste collection; b) Sorting out items made of polystyrene, polyamide, polypropylene, metal, paper and wood, thus providing post-consumer plastic materials; c) sorting out the colored articles, thereby providing a first intermediate stream of substantially colorless products and a second intermediate stream of substantially white products; d) Sorting out impurities through manual inspection; e) receiving therefrom two streams of polyethylene material, a first stream being substantially transparent and a second stream being substantially white; f) grinding the two streams separately, washing in aqueous solutions with various detergents and subsequently drying and screening to produce two pretreated streams; g) further sorting the two pretreated streams to eliminate non-polyolefin and colored fractions respectively; h) extruding into granules; i) Aeration at a temperature in the range of 100 to 130°C.
12. The polyethylene blend according to any one of claims 1 to 4 in the form of particles.
13. An article made from the polyethylene blend according to any one of claims 1 to 12.
14. The article of claim 13, wherein the polyethylene blend comprises at least 95 weight percent of the reactants used to make the article.
15. The article of claim 14 which is a bottle.
16. A blend comprising the polyethylene blend according to any one of claims 1 to 12 and at least one virgin polyolefin and / or recycled polyolefin.
17. Use of the polyethylene blend according to any one of claims 1 to 12 for packaging.
Citation Information
Patent Citations
Process for removing volatiles from post-consumer recycled polyolefin chips
US5767230A
Method for producing polyolefin recyclates
WO2018046578A1
Process for the production of polyolefin recyclates
DE102016116742A1
Recycling of high-density polyethylene from domestic polymer waste
EP2697025A1
Nucleated polyethylene blends and their use in molded articles
JP2019529649A